The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ijid.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors Drug Resistance Mutations in Turkish Patients with Chronic Hepatitis C

Abstract: We are of the opinion that drug resistance analyses can be beneficial and necessary in revealing which variants are responsible for pre-treatment natural resistance and which mutations are responsible for the viral breakthrough that may develop during the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
2
0
4
Order By: Relevance
“…Regardless of genotype and exposure to treatment, resistance mutations against DAAs were found in HCV isolates worldwide, as proofed by studies conducted on sequence databases (25,26). Furthermore, studies have shown the presence of DAAs resistance mutations in different unexposed populations (27,28). However, there are no clear indications for baseline screening of NS3 PIs resistance mutations in the absence of prior PIs exposure, nevertheless clinicians should be aware of Q80K polymorphism in 1a subtype isolates and resistant variants at positions 155, 156 and 168 in genotype 1 isolates (29).…”
Section: Discussionmentioning
confidence: 87%
“…Regardless of genotype and exposure to treatment, resistance mutations against DAAs were found in HCV isolates worldwide, as proofed by studies conducted on sequence databases (25,26). Furthermore, studies have shown the presence of DAAs resistance mutations in different unexposed populations (27,28). However, there are no clear indications for baseline screening of NS3 PIs resistance mutations in the absence of prior PIs exposure, nevertheless clinicians should be aware of Q80K polymorphism in 1a subtype isolates and resistant variants at positions 155, 156 and 168 in genotype 1 isolates (29).…”
Section: Discussionmentioning
confidence: 87%
“…The Y93H is a mutation related to cross-resistance in the NS5A inhibitor group (34). However, Y93H mutation was the first case to be reported in Turkey (35,36). These findings suggested the resistance analysis, as experienced in CHC patients on therapy should remain a basic part of the management.…”
Section: Discussionmentioning
confidence: 99%
“…Ciddi fibrozu olan hastalar da siroz açısından klinik (splenomegali, karında asit, portal hipertansiyon, özofagus varisi, palmar eritem, periferik telanjiyektaziler) ve laboratuvar (serum bilirübin ve albümin değerleri, protrombin zamanı) olarak değerlendirilmelidir (57)(58)(59). İleri derecede fibrozu (METAVIR skoru F3/4 evresinde) olan sirotik hastalar HSK gelişmesi açısından 6 ayda bir izlenmelidir (51,60).…”
Section: Karaciğer Hastalığının şIddeti Ve Bazal Virolojik Parametrelerunclassified
“…Ayrıca doğal dirençlerin KVY üzerine önemli bir etkisi de gösterilmemiştir. Bu nedenle tedavi öncesinde rutin direnç analizi yapılması bugün için önerilmemektedir (51,60,61 …”
Section: Karaciğer Hastalığının şIddeti Ve Bazal Virolojik Parametrelerunclassified
See 1 more Smart Citation